The automated operational control system for the food industry - Sidletskyi, Victor (My University, 2016)
Process food industries represents all measures in which mass, energy and information are transported, transformed or stored. Control system for a process processing industry, in general represents, control elements, sensors and actuators are assigned to the process, they form the base of observation, visualization, diagnosis of the process and the actuators possess the task of intervening into the process in order to achieve the desired result.
Keywords: food industry; control system; operative management; харчова промисловість; система управління; оперативний менеджмент; пищевая промышленность; система контроля; оперативный менеджмент; кафедра автоматизації та комп'ютерних технологій систем управління ім. проф. А.П. Ладанюка